University Education Management System Exploration and Practice Based on Big Data Analysis from the perspective of Humanism. Issue 4 (February 2021) - Zhang, Xun; Lin, Dayong
Abstract: At present, the lack of humanism in my country's higher education management concepts and models is a direct manifestation of the lack of humanism in my country's higher education management mechanisms and activities. There are many reasons for this problem, including the negative influence of traditional culture, the negative influence of the market economy and the defects of education management mechanism. Therefore, we should establish a "people-oriented" education management concept."With the support of Internet information, by strengthening the personality shaping of the main body of education management, we will carry out people-oriented education management activities to help Chinese universities build education management under the "people-oriented" concept system". This article first analyzes the necessity of implementing education management system in universities from the big data. Then, the current problems are analyzed. Finally, some suggestions were made.